Static behaviour up to failure of a full-scale GFRP-concrete hybrid footbridge. (15th November 2019) - Jurkiewiez, Bruno; Koaik, Alaa; Bel, Sylvain
Highlights: Experimental investigation on the short-term behaviour up to failure of a full-scale GFRP-concrete hybrid footbridge. Mixed bonding/bolting connection. Centered and eccentric loading. Shear failure in the GFRP profile at the junction between the web and the flange. Abstract: This paper presents an experimental investigation on the short-term behaviour up to failure of a full-scale GFRP-concrete hybrid footbridge. The connection between the slab and the GFRP profiles is a mixed bonding/bolting connection. The footbridge was first tested in the elastic domain under different configurations to mobilize the flexural and torsional stiffness. The numerous measurements show that the behaviour is in accordance with the regulatory requirements at SLS. The footbridge was finally loaded up to failure. The shear failure obtained in the GFRP section showed that the mixed connection used played its role perfectly and made it possible to fully exploit the bending capacity of the structure. In addition, the comparison with the results of the beam tests shows that the two-beam bridge can be analysed with sufficient precision as the juxtaposition of the two single-sided beams. This study confirms the important capacity of these hybrid GFRP-concrete structures in the construction of bridges or footbridges with classical engineer design tools.